Cross-cultural applicability of the Medical Outcomes Study – Social Support Survey as a measure of perceived social support among Greek-Cypriot mothers Psychometric validation of MOS - Nicolaou, Christiana; Kouta, Christiana; Papathanassoglou, Elizabeth; Middleton, Nicos (My University, 2014)
Several studies link social support with psychosocial and physical well-being; nevertheless, the way social support is conceptualized and operationalized differs widely between studies. Some tools focus on structural (social network) or proxy measures such marital status while others on functional aspects of support, such as the Medical Outcomes Study - Social Support Survey (MOS-SSS) questionnaire. Furthermore, the cross-cultural applicability of such measures has not always been established. METHODS: A descriptive comparative study was performed with a purposive sample of 52 mothers of children with cancer and 208 mothers of age- and gender-matched children without chronic illness in order to assess the psychometric properties of the Greek translation of the 19-item MOS-SSS. Differences in perceived social support (overall and by type) between the study groups and by socio-demographic characteristics was investigated in regression models. RESULTS: A clear structure was observed explaining 79% of the total variance – tangible (4 items, Cronbach’s α=0.92), emotional/informational (8 items, α=0.95) and positive social interaction/affectionate support (7 items, α=0.96). Consistently lower social support was reported by unmarried/divorced mothers, those with lower income, financial difficulties, not owning their house and higher residential mobility, a further support of the known-group validity of the tool. While no significant differences were observed in terms of overall perceived social support between the study groups, caregivers of children with cancer tended to report lower emotional/ informational support but higher tangible support, lending support to the tool’s scale discriminant validity. Family was identified as the main source of support by both groups, followed by friends (in controls) and other parents of children with cancer (in cases).CONCLUSIONS: The MOS-SSS appears to be a valid and reliable measure of functional aspects of social support among Greek-speaking Cypriot mothers, further supporting the cross-cultural applicability of the tool and its use in cross-national epidemiological studies.
Keywords: Mothers; Children; Cancer; Social support; Psychometric validation